Synthesis, Characterization And Properties Of Chitosan-Poly (Methacrylic Acid-Co-N-Isopropylacrylamide) Hydrogel For Drug Delivery - Md Rasib, Siti Zalifah (2019)
The application of chitosan has received enormous attention in medical field particularly in drug delivery. In this study, chitosan with two monomers, methacrylic acid (MAA) and N-isopropylacrylamide (NIPAM) were prepared by emulsion polymerization to form a chitosan-poly(methacrylic acid-co-N-isopropylacrylamide) (chitosan-p(MAA-co-NIPAM)) hydrogel as a drug carrier. Hydrogels were characterized using Fourier Transform Infrared (FTIR) Spectroscopy, Carbon-13 Nuclear Magnetic Resonance (13C-NMR), Field Emission Scanning Electron Microscope (FESEM), particle size analysis and Dynamic Light Scattering (DLS). The effect of stimuli responsive (pH and temperature), hydrolysis, drug loading, in-vitro drug release and cytotoxicity was investigated. The finding found that chitosan-p(MAA-co-NIPAM) hydrogel synthesized using surfactant (Span 80) successfully achieved particle size less than 500 nm. The cationic surface charge of synthesis hydrogel passed the stability requirement to avoid aggregation in blood system above 30 mV at pH 3 to 5 and potentially enhanced cellular internalization drug delivery up to pH 6. The release of Rifampicin drug was controlled by combination of diffusion and swelling as the drug released was prolonged to 72 hours indicating that the hydrogel responded to the pH and temperature environment. High viability cell from cytotoxicity assessment demonstrated that the hydrogels are human/animal friendly biomaterials. Thus, it can be concluded that chitosan-p(MAA-co-NIPAM) hydrogels are feasible as controlled drug delivery carrier.